High performance flexible micro-supercapacitor for powering a vertically integrated skin-attachable strain sensor on a bio-inspired adhesive. (May 2021) - Park, Hyojin; Song, Changhoon; Jin, Sang Woo; Lee, Hanchan; Keum, Kayeon; Lee, Yong Hui; Lee, Geumbee; Jeong, Yu Ra; Ha, Jeong Sook
Abstract: We report on the fabrication of a high performance flexible micro-supercapacitor (MSC) for powering a vertically integrated skin-attachable strain sensor on a gecko-inspired micro-structured adhesive. Combined utilization of the mixed manganese/vanadium (Mn/V) oxide grown on MWCNT electrode and the sulfone-based electrolyte, PC/SL/LiClO4 /PMMA, enhances both the capacitance and operation voltage up to 2 V of MSC. Thus, the fabricated MSC exhibits excellent electrochemical performance with an areal capacitance of 11.8 mF cm − 2 and an areal energy density of 6.58 µWh cm − 2 at an areal power density of 200 µW cm − 2 . The MSC shows mechanical stability over 1000 repetitive bends at a bending radius of 3.7 mm. The strain sensor made of fragmentized graphene foam embedded in PDMS film provides a high gauge factor of 12.6 up to 50% strain to detect strains due to various bio-signals. Our gecko-inspired adhesive made of PDMS micropillars inked with a mixture of PDMS and Silbione to have spatula tips exhibits not only high adhesion property but also high durability over repeated cycles of attachment-detachment and negligible skin irritation. After vertical integration of the MSC, strain sensor, and the adhesive film, bio-signals such as an arterial pulse, swallowing, and frowning of the brow are successfully detected using energy stored in the MSC. Graphical Abstract: ga1 Highlights: High-performance micro-supercapacitor (MSC) was fabricated with mixed metal oxide electrode and sulfone-based electrolyte. Mixed oxide electrode enhanced the capacitance and sulfone-based electrolyte widened operation voltage window of MSC. Skin-attached fragmentized graphene foam strain sensor with a micro-structured adhesive detected bio-signals. The strain sensor was operated using the stored energy of the vertically integrated MSC. MSC was demonstrated as an integrated energy storage device for bio-signal monitoring.